The Rosehip Plant and Medicinal Properties - Sulaymonov Egamberdi Tilavoldi o’gli; Saidov Saidislom Saidabror o’gli (American Journal of Biology and Natural Sciences, 2025)
The rosehip plant (Rosa canina), commonly known as wild rose fruit, is one of the most valuable medicinal plants due to its rich content of vitamin C, antioxidants, flavonoids, and essential nutrients. Numerous scientific studies confirm its strong anti-inflammatory, immune-boosting, antioxidant, and cardiovascular-supporting properties. In Uzbekistan, rosehip has long been used in traditional herbal medicine for strengthening immunity, treating colds, improving digestion, and supporting overall health. Today, it is widely consumed in the form of tea, syrup, jam, oil, and medicinal preparations. This paper discusses the medicinal properties of rosehip, its health benefits, and its significance within the Uzbek context.